2010
DOI: 10.1016/j.jqsrt.2010.06.012
|View full text |Cite
|
Sign up to set email alerts
|

IUPAC critical evaluation of the rotational–vibrational spectra of water vapor. Part II

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 196 publications
(115 citation statements)
references
References 140 publications
2
106
0
7
Order By: Relevance
“…This was done by comparison with spectroscopic databases [3,33]. As shown below, this step also allowed us to calibrate the observed spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was done by comparison with spectroscopic databases [3,33]. As shown below, this step also allowed us to calibrate the observed spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…This line list was calculated using DVR3D [34], the very recent spectroscopically-determined potential energy surface (PES) of Bubakina et al [35], and the high accuracy LTP2011 dipole moment surface (DMS) of Lodi et al [36]. This line list has the unusual feature that the computed energy levels are replaced by empirically-determined ones from the IUPAC TG [3] [21,22]. Comparison showed that this line list was much less reliable for all but the strongest lines.…”
Section: Data Sourcesmentioning
confidence: 99%
See 3 more Smart Citations